The environmental justice reader : politics, poetics, & pedagogy - Adamson, Joni, 1958-; Evans, Mei Mei; Stein, Rachel, 1954- (University of Arizona Press, 2002)
A collection of essays on the environmental justice movement, examining the various ways that teaching, art, and political action affect change in environmental awareness and policies.